Carotid intima media thickness as a marker of subclinical atherosclerosis in rheumatoid arthritis: a case control study - Saigal, Renu; Mathur, Vivek; Goyal, Laxmikant (International Journal of Advances in Medicine, 2016)
Background: Increased cardiovascular morbidity and mortality has been observed in rheumatoid arthritis (RA) because of accelerated atherosclerosis. We measured carotid intima-media thickness (CIMT) as a surrogate marker of subclinical atherosclerosis in RA in this study. Methods: In this study 40 cases of RA and 26 matched individuals were recruited. CIMT measurements were done using B-mode ultrasound. Disease activity was assessed using DAS28, C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) levels. Results: Mean age of the study groups was 52.45±7.43 years (range 41-69 years). Average disease duration was 9.34±4.18 years (range 5-20 years). Thirty two (32/40, 80%) cases of RA were RF positive. ESR was significantly higher in RA cases (51.75±24.13 mm Ist hr) compared to healthy controls (17.31±9.08 mm Ist hour, p <0.001). Significantly increased CIMT was observed in cases as compared to the control group (0.68 ± 0.06 mm versus 0.63±0.07; ???? 0.002). CIMT in the cases positively correlated with age (???? = 0.500; 0.001), duration of disease (????= 0.594; ???? 0.001). CIMT negatively correlated with HDL (???? = -0.345; 0.029). Conclusions: Subclinical atherosclerosis (increase CIMT) is common in RA and correlated well with disease duration. So every patient of RA should be evaluated for development for atherosclerosis.